VD_FINDINFO Décision / 2012 / 862 vom 15. Oktober 2012 - VD Tribunal cantonal (2012)
DÉPENS, DÉCISION SUR FRAIS | 69 al. 1bis LAI, 61 let. a LPGA, 61 let. g LPGA, 49 LPA-VD, 55 LPA-VD, 94 al. 1 let. a LPA-VD